(untitled) (Ozone Therapy Global Journal, 2022)
We present the case of an adult female patient in her fourth decade of life with a history of interstitial pneumonia that began with systemic symptoms, skin lesions on the hands called "mechanic’s hands", muscle weakness and polyarthralgia. Through some laboratory, cabinet and physical examination studies, antisynthetase syndrome is suspected. We present the case of an adult female patient in her fourth decade of life with a history of interstitial pneumonia that began with systemic symptoms, skin lesions on the hands called "mechanic’s hands", muscle weakness and polyarthralgia. Through some laboratory, cabinet and physical examination studies, antisynthetase syndrome is suspected. In this sense, ozone therapy was incorporated as a complement, considering that it is a treatment that does not cause side effects, allergies, interaction with other drugs, it is easy to apply and low cost, which makes it an excellent therapy. Objective: To present a clinical case in which ozone therapy was used as a second-choice treatment in antisynthetase syndrome after symptoms had appeared and without a favorable response to treatment with first-choice corticosteroids. Conclusion: Ozone therapy as a complementary treatment showed effectiveness in reducing the symptoms of antisynthetase syndrome, finding gradual improvement